Rethinking Digital Media and Citizenship: Conditions, Contexts, and Consequences. (July 2018) - Nah, Seungahn; Yamamoto, Masahiro
This special issue presents a total of seven articles concerning digital media and citizenship in various political, civic, and cultural contexts. Specifically, the entire collection investigates how digital media use and civic engagement can be conceptualized, operationalized, and theorized in the current digital media environment. The seven studies further examine how the use of traditional and newer forms of media influences civic engagement across communities of places, interests, and practices as well as different social groups at the local and global levels. With an interest in social conditions and contexts surrounding the civic utility of digital media, this special issue brings a unique perspective to the existing scholarship and provides new venues for continued scholarly attention to this important subject.